Tumor-Educated Neutrophils Activate Mesenchymal Stem Cells to Promote Gastric Cancer Growth and Metastasis - Zhang, Jiahui; Ji, Cheng; Li, Wei; Mao, Zheying; Shi, Yinghong; Shi, Hui; Ji, Runbi; Qian, Hui; Xu, Wenrong; Zhang, Xu (Frontiers in Cell and Developmental Biology, 2020)
In response to tumor signals, mesenchymal stem cells (MSCs) are recruited to tumor sites and activated to promote tumor progression. Emerging evidences suggest that in addition to tumor cells, non-tumor cells in tumor microenvironment could also interact with MSCs to regulate their phenotype and function. However, the mechanism for MSCs regulation in gastric cancer has not been fully understood. In this study, we reported that tumor-educated neutrophils (TENs) induced the transformation of MSCs into cancer-associated fibroblasts (CAFs) which in turn remarkably facilitated gastric cancer growth and metastasis. Mechanistic study showed that TENs exerted their effects by secreting inflammatory factors including IL-17, IL-23 and TNF-α, which triggered the activation of AKT and p38 pathways in MSCs. Pre-treatment with neutralizing antibodies to these inflammatory factors or pathway inhibitors reversed TENs-induced transformation of MSCs to CAFs. Taken together, these data suggest that TENs promote gastric cancer progression through the regulation of MSCs/CAFs transformation.